PENERAPAN KEPEMIMPINAN KEPALA SEKOLAH BERWAWASAN MULTIKULTURAL DALAM PENCEGAHAN KEKERASAN SISWA - S, Syahril Rizal; Irianto, Petrus; Kurniawan, Diki; Kusdianto, Kusdianto; Tanta, Tanta; Masreng, Robert; Mataputun, Yulius (SECONDARY: Jurnal Inovasi Pendidikan Menengah, 2026)
Complex sociocultural challenges and ethnic heterogeneity in the vocational high school environment in Papua often trigger the emergence of violence between students. This study aims to analyze in depth the implementation of multicultural leadership of the principal to prevent violence at SMKS YPK TIK Serui, Yapen Islands Regency. The focus of the study includes the development of democratic attitudes, internalization of the diversity paradigm, enforcement of anti-discrimination principles, and development of gender sensitivity. The research method used is a mixed method explanatory sequential design through the distribution of questionnaires to fifty student respondents and interviews with nine key informants. Quantitative findings show that multicultural leadership indicators are in the moderate category, with an anti-discrimination score of 66.91%, diversity paradigm 63.20%, gender sensitivity 62.80%, and democratic attitudes 58.60%. The novelty of this study lies in the integration of Papuan local wisdom, namely Three Stones One Furnace, into the school managerial system. Supporting factors include foundation support, while obstacles include the influence of alcohol. As a result, physical violence was successfully reduced by 62.7%, but a new challenge emerged in the form of digital violence, which increased by 67%. The study's conclusions confirm that multicultural leadership based on restorative justice is highly effective in significantly reducing physical aggression. However, educational institutions need to strengthen systemic multicultural digital literacy strategies to address the increasingly complex dynamics of violence in the digital era and to create sustainable school harmony. ABSTRAK Tantangan sosiokultural dan heterogenitas etnis yang kompleks di lingkungan Sekolah Menengah Kejuruan wilayah Papua sering kali memicu munculnya fenomena kekerasan antarsiswa. Penelitian ini bertujuan untuk menganalisis secara mendalam penerapan kepemimpinan kepala sekolah berwawasan multikultural guna mencegah kekerasan di SMKS YPK TIK Serui, Kabupaten Kepulauan Yapen. Fokus kajian meliputi pembangunan sikap demokratis, internalisasi paradigma keragaman, penegakan prinsip anti-diskriminasi, serta pengembangan sensitivitas gender. Metode penelitian yang digunakan adalah metode campuran desain sekuensial eksplanatori melalui penyebaran angket kepada lima puluh responden siswa dan wawancara sembilan informan kunci. Temuan kuantitatif menunjukkan indikator kepemimpinan multikultural berada pada kategori sedang, dengan skor anti-diskriminasi 66,91%, paradigma keragaman 63,20%, sensitivitas gender 62,80%, serta sikap demokratis 58,60%. Kebaruan penelitian ini terletak pada integrasi kearifan lokal Papua yakni Tiga Batu Satu Tungku ke dalam sistem manajerial sekolah. Faktor pendukung melibatkan dukungan yayasan, sementara hambatan mencakup pengaruh minuman keras. Dampaknya, kekerasan fisik berhasil ditekan hingga tingkat 62,7%, namun muncul tantangan baru berupa kekerasan digital sebesar 67%. Simpulan penelitian menegaskan bahwa kepemimpinan multikultural berbasis keadilan restoratif sangat efektif dalam mereduksi agresi fisik secara signifikan, akan tetapi institusi pendidikan memerlukan penguatan strategi literasi digital multikultural yang sistemik untuk menghadapi dinamika kekerasan di era digital yang semakin kompleks demi terciptanya harmonisasi sekolah secara berkesinambungan.